2021
DOI: 10.1007/s00540-021-02897-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of critically ill patients with COVID-19 in Kobe, Japan: a single-center, retrospective, observational study

Abstract: Purpose Coronavirus disease 2019 (COVID-19) has placed a great burden on critical care services worldwide. Data regarding critically ill COVID-19 patients and their demand of critical care services outside of initial COVID-19 epicenters are lacking. This study described clinical characteristics and outcomes of critically ill COVID-19 patients and the capacity of a COVID-19-dedicated intensive care unit (ICU) in Kobe, Japan. Methods This retrospective observational study included critically ill COVID-19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…It was also significantly shorter than 6−7 days reported in a large cohort study in Japan [ 16 ], suggesting rapid deterioration of respiratory condition despite prompt admission from the onset of symptoms. Commonly observed symptoms were fever, cough, and fatigue, in consistent with previous studies [ 3 , 10 , 16 ]. Note that more than 60% of patients with moderate II severity did not complain of dyspnea, suggesting the possibility of asymptomatic hypoxia [ 17 ] and the importance of routine measurement of SpO2 regardless of the complaints of patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was also significantly shorter than 6−7 days reported in a large cohort study in Japan [ 16 ], suggesting rapid deterioration of respiratory condition despite prompt admission from the onset of symptoms. Commonly observed symptoms were fever, cough, and fatigue, in consistent with previous studies [ 3 , 10 , 16 ]. Note that more than 60% of patients with moderate II severity did not complain of dyspnea, suggesting the possibility of asymptomatic hypoxia [ 17 ] and the importance of routine measurement of SpO2 regardless of the complaints of patients.…”
Section: Discussionsupporting
confidence: 91%
“…After publication of our report regarding the first and the second waves of COVID-19 outbreak before September, 2020 [ 3 ], there have been three larger waves [ 4 ], characterized by the predominance of variants of severe acute respiratory distress coronavirus 2 (SARS-CoV-2) with higher transmissibility than the pre-existing one, and an increase of the number of elderly patients [ 4 , 5 ], which made the medical system in crisis [ 6 8 ]. Although epidemiological information on the COVID-19 outbreak has been disseminated by the government as well as by each prefecture in Japan [ 4 , 9 ], there is a paucity of data from the viewpoint of hospitals [ 3 , 10 , 11 ], which will provide new insight into and a better guidance for managing the admission and transfer of patients during the COVID-19 pandemic. In this study, we retrospectively analyzed the clinical characteristics of patients with confirmed COVID-19 in our hospital in the third wave, elucidated the causes of deterioration of the respiratory condition, and examined the differences with those during the previous outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a total of 61 peer-reviewed studies were included in the final analysis (Fig. 1A) 10,12,13,21–78 . Of these final 61 studies, 11 studies were conducted in China, 3 were conducted in America (2 studies from South America and 1 study from Central America), 17 involved centers in the United States, 16 involved centers in Europe, 3 involved centers in Canada, 9 involved centers in Asia, and 2 were based on multinational collaborations (one was between the United Kingdom and Ireland, and the second was between the United States, Europe, Canada, and Japan).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, most of the mechanically ventilated COVID-19 patients in the city were preferentially admitted or transferred to KCGH. Our surge capacity strategies and patient management during the first 3 months of the city’s COVID-19 outbreak have been described in our previous study [ 21 ]. Our patient management during the study period was generally based on the guidelines in place at the time.…”
Section: Methodsmentioning
confidence: 99%